Analysis of Trans-Mebidang Bus Rapid Transit (BRT) Policy Implementation in North Sumatra - Muhammad Nizam; Rahim Matondang; Badaruddin Badaruddin (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Trans Mebidang is a Bus Rapid Transit (BRT) system in North Sumatra Province which operates in Medan City, Binjai City, and Deli Serdang Regency. According to the Research and Development Center for Land and Railways at the Ministry of Transportation of the Republic of Indonesia in 2014 the traffic density level in Medan City reached a V / C ratio of 0.769, this has an impact on inconvenience and increases travel time for road users. This study aims to determine the extent of the implementation of the governor's regulations and to determine the supporting and inhibiting factors for the implementation of the Trans Mebidang Bus Rapid Transit (BRT) policy in breaking down congestion in Medan City. In this study, researchers used descriptive methods with observation data collection techniques, interviews and literature studies. The data analysis technique used in this research is analysis using transcripts of the results of interviews, data reduction, analysis, data interpretation and triangulation.The results of the study, researchers found a phenomenon in the field that the implementation of policies in the Regulation of the Governor of North Sumatra Number 31 of 2014 concerning Road-Based Mass Public Transportation Services in the Urban Areas of Medan, Binjai and Deli Serdang. Based on the research focus set in accordance with Edward III's theory, the researcher can conclude that the supporting and inhibiting factors are influenced by aspects of communication, resources, disposition and bureaucratic structure, this can be seen in the summary of the research results that have been presented by the researcher in writing this thesis.